Pengaruh perbedaan warna lampu terhadap laju pertumbuhan spesifik benih ikan Lele Dumbo (Clarias gariepinus) - Irawadi Gunawan; Ummi Suraya (Fakultas Peternakan Universitas Kristen Palangka Raya, 2019)
The purpose of this study was to determine the effect of different lamp colors. on the specific growth rate of African catfish (Clarias gariepinus) seeds. This study used a Completely Randomized Design (CRD) with 3 replications using 3 treatments. The treatments used are different light colors on the media used for the maintenance of African catfish seeds, namely: M (Red), KN (Yellow), and H (Green). The results of the statistical analysis showed that the different colors of the lights did not have a very significant effect on the specific growth rate of African catfish seeds. Average specific growth rate (SGR) 1.570 - 1.899% BW / day, with a red sequence of 1,899; yellow 1,782; green 1,642 and control 1,570. BW / day. The results showed that the red color had a strong influence on the specific growth rate of African catfish seeds compared with the yellow, and green colors and controls. The survival data shows the average life results of the control treatment and the color of the lights ranging from 44 - 69 with the best order is the red light 69; green 64; yellow 57 and control 44. The treatment of different colors of lights had a significant effect on the survival of African catfish seeds. The calculation of the average feed conversion (FCR), namely for red light aquarium color = 3.02; yellow = 3.52; green = 3.40 and control = 4.49. The treatment of lamp color differences has a significant effect on the conversion ratio of feed given to African catfish seeds. Water quality in the experimental media is still within reasonable limits for the maintenance of African catfish seeds 5.36 - 6.69 ppm for dissolved oxygen content; 25.6 - 27.80 C for water temperature and 8.21 - 8.50 for the degree of acidity (pH) of water. Water quality greatly influences or has a significant correlation to the value of Specific Growth (SGR). Keywords : Light color, African Catfish (Clarias gariepinus), growth rate.